A Mixed Bi-level Model to Correspond Service Recovery Chain - Abdolalipour, Amirhossein; Nazemi, Jamshid; Toloie Eshlaghi, Abbas; Hosseinzadeh Lotfi, Farhad (International Review of Management and Marketing, 2017)
In the competitive environment, minimizing time space between service failure perception and service recovery with lowest cost is one of fast responsiveness company's requirements. In this article, modeling service failure response time is considered. It was not only service recovery chain profit optimization carefully planned but also satisfaction of consumers who disturbed by a service failure was considered profoundly. Inconsistency between optimization of service recovery chain's total benefit and existing firm's local benefit was modeled by bi-level programming approach. The Core recovery firm or department plays leader character and in lower level there are firms or departments as followers that make local decisions in service recovery chain. In this article, a heuristic algorithm was developed to solve the model. Keywords: Bi level programming, service recovery, Service chain JEL Classifications: C6, L2